Winter condition, physiology, and growth potential of juvenile Antarctic krill - Bernard, Kim S.; Steinke, Kirsten B.; Fontana, Julia M. (Frontiers in Marine Science, 2022)
In recent years, substantial efforts have been made to understand the implications of climate change on Antarctic krill, Euphausia superba, because of their pivotal role in the Southern Ocean food web and in biogeochemical cycling. Winter is one of the least studied seasons in Antarctica and we have limited understanding about the strategies Antarctic krill use to survive the winter. In particular, data on the winter physiology and condition of juvenile Antarctic krill are severely lacking. From May to September (the austral autumn-winter) of 2019, we maintained juvenile Antarctic krill in large (1,330 L) aquarium tanks at Palmer Station, Antarctica and, at monthly time intervals, measured their physiology and condition. Each tank served as a “food environment scenario”, representing possible food environments the krill may encounter during winter along the Western Antarctic Peninsula. We found that, unlike adults, juvenile krill maintain relatively high respiration rates through the winter and respond positively to increased food concentrations by increasing their ingestion rates. Unlike larval krill, juveniles use lipid stores accumulated during the summer and autumn to sustain themselves through periods of starvation in the winter. We used our empirically derived measurements of physiology and condition to estimate the energy budget and growth potential of juvenile krill during the winter. We found that, given their comparatively high respiration rates, small juvenile krill (20 mg dry weight) would need to encounter food at concentrations of ~ 0.15 mg C L-1 daily to avoid loss of body carbon. Without sufficient lipid reserves, this value increases to ~ 0.54 mg C L-1, daily. The health of juvenile krill in the wintertime is dependent on their ability to accumulate lipid stores in the summer and autumn and to find sufficient food during the winter. Changes in food availability to Antarctic krill throughout the year may become problematic to juvenile krill in the future. Understanding the variability in the winter energy budget of juvenile Antarctic krill will allow us to improve population models that make assumptions on seasonal growth patterns.